Karakter Membangun Kristen dalam Perspektif Filsafat Pendidikan Agama Kristen - Wilson Simanjuntak; Lesti Simanjuntak; Renti Ardina Gajah; Lidia Kando Hutapea; Shinta Mariana (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study aims to examine the importance of Christian Religious Education philosophy in shaping strong Christian character in students and the integration of Biblical values in the learning process. The research method used is descriptive, which outlines the application of Christian education principles and their impact on students' character. The findings of the study show that Christian Religious Education prioritizes the development of spiritual, moral, and social aspects, with key principles such as love, forgiveness, and integrity. Through the implementation of these values, students not only develop intellectually but also build character in accordance with Christ's teachings, making them wise individuals in decision-making and positively impacting their communities and surrounding environments.